First Morpheme in Compound Words in Modern Chinese (Words from Coronavirus Era) - Xiaoge Li (Научный диалог, 2022)
The article is devoted to the study of the principles of the formation of abbreviated words and the establishment of semantic and syntactic relationships between their constituent parts using the example of new abbreviated words that appeared with the onset of the coronavirus pandemic. The words recorded in the Chinese language in 2020—2021 are analyzed. Particular attention is paid to the principle of selecting the first morpheme, in which the first morphemes of the original significant segments are preserved to form an abbreviated form. The relevance of the study is due to the increasing number of new abbreviated words, the complexity of their word-formation structures and the importance of their adequate understanding by both native Chinese speakers and foreign students. 12 compound abbreviated words (4 single-level and 8 multi-level) were analyzed, naming current phenomena in the life of Chinese society in the era of coronavirus. Five types of semanticsyntactic connections have been established: attributive connection, copulative connection, verbal-object connection, resultative connection and subject-predicative connection. It is concluded that among the principles on the basis of which complex abbreviated words are formed in modern Chinese, such as equivalence, distinctiveness, familiarity, etc., the principle of selecting the first morpheme plays an important role.